CHOICE OF GOAL AND PERFORMANCE CRITERIA OF THE DESIGNED SYSTEM - Zhanys A.B Жаныс А.Б; Rudy D.V. Руды Д.В. (Рroblems of engineering and professional education, 2023)
Test media are providing high performance and quality of the functioning of various computer programs and software systems, which in its diversity to the international standards, developed with the participation of representatives of the leading companies in the industry all different directions